Identification And Farmer Family's Preference Of Indigenous Food In Rural Bengkulu - Betty Yosephin Simanjuntak; Desri Suryani; Miratul Haya; Ali Khomsan (poltekkes kemenkes mataram, 2020)
Indigenous food can be said as a local identity because of its existence as part of the culture of the community, such as certain procedures in processing their food, its role in community culture and governance, and recipes that are maintained from generation to generation. Purpose of this research was to identify the kinds of traditional foods, preferences in the consumption pattern in the family of farmers. FGD was performed on each ethnic group, and the members were mothers who understood the traditional foods consumed by people in the related ethnic group and they resided in the ethnic group. Most of the food sources of vegetables consumed by the community were vegetables that many people got from rice fields/dryfields/ gardens Traditional food snacks, side dishes and vegetables in the agricultural households as such as bolu semut, rebung asam ikan gaguk, guasan, gulai nangko,and gulai jamur gerigit.